Homomeric and heteromeric α7 nicotinic acetylcholine receptors in health and some central nervous system diseases - Borroni, María Virginia (2021)
Fil: Borroni, María Virginia. Universidad de Buenos Aires. Instituto de Tecnología en Polímeros y Nanotecnología; Argentina